How tobacco makes room in rice based cropping systems of Bangladesh - Shahidullah, S M; Ibrahim, M; Quais, M K; Pramanik, S; Zaman, M A U; Shirazy, B J; Mostafizur, A B M; Chakrobarty, T; Uddin, M E; Aziz, M A; Rana, M M; Iqbal, M (Bangladesh Rice Journal, 2025)
In spite of hazardous nature, tobacco has a significant position in the cropping system of Bangladesh. The existing status and determinants related to tobacco cultivation in Bangladesh remain inadequately explored. A thorough survey among farmers was conducted in 2021 to assess tobacco cultivation. The total tobacco cultivation area in Bangladesh was documented as 49 thousand hectares, accounting for approximately 0.57% of the overall net cropped area. Tobacco is distributed in 14 cropping patterns and cultivation is concentrated in 45 Upazilas of 15 districts. Farmers consider tobacco farming as a business and as a guaranteed cash crop at a pre-declared price rate. Poor farmers explore the opportunity of family labour employment in tobacco production and processing. Farmers are driven towards engaging in the business by a range of incentives offered by tobacco companies, while the fluctuating market prices of winter vegetables serve as an additional motivator. Many farmers perceive the risks associated with tobacco as being at a negligible level. Minimizing uncertainties of traditional agriculture may turn some farmers from tobacco to traditional crops. Bangladesh Rice J. 27(2): 25-38, 2023